Effect of Pre-Vulcanization Time on Structure and Thermal Insulation of Natural Rubber Latex/Silica Aerogel Composites - Boonrawd, Chayanan; Vittayakorn, Wanwilai; Triampo, Darapond; Yodyingyong, Supan (My University, 2026)
Polymer/Silica aerogel (SA) composites improve mechanical properties strategically, but the mixing process disrupts the aerogel’s structure, reducing its efficiency due to polymer chains filling the pores. Pre-vulcanized natural rubber latex (PVNRL) with a higher crosslink density can strain the moving chains, thereby preserving the SA-porous structure in the bulk composite for thermal insulation materials. This study aimed to investigate the effects of PVNRL pre-vulcanization time and SA-immersion time in PVNRL. For PVNRL/SA composite preparation, various PVNRL, from 0 days to 8 days of pre-vulcanization time, were mixed with a fixed SA content of 20 parts per hundred of rubber (phr) using a latex compounding method. Subsequently, the PVNRL/SA slurries were cast on glass plates with 0, 3, and 6 days to obtain the PVNRL/SA composite. Considering the effect of pre-vulcanization time, the crosslink density of the composite increased and revealed a peak at PVNRL/SA with 8-day PVNRL by 7.277 ± 0.881 μmol (Formula presented.), corresponding to the closest percentage of pore area in the SA’s structure to the pristine SA, and eventually a 42.41% lower thermal conductivity than the PVNRL/SA with 0-day PVNRL exhibited. In addition, the thermal conductivity increased more slowly over immersion time with the presence of 8-day PVNRL. The proposed correlation states that increasing the pre-vulcanization improves the thermal insulation performance of PVNRL/SA composites, emphasizing the reduction of filled SA’s pore with unvulcanized NR chains. Furthermore, the PVNRL/SA composite with 8-day PVNRL maintains thermal stability at 387.3 °C, and can be flexed at room temperature. These fascinating discoveries may be advantageous for further applications related to thin-film and flexible thermal insulation materials.
Keywords: natural rubber latex; pre-vulcanization; silica aerogel; thermal insulation materials